Science in the bet midrash : studies in Maimonides - Kellner, Menachem Marc, 1946- (Brighton, MA : Academic Studies Press, 2009)
This book explores the religious thought of Moses Maimonides (1138-1204), the single most influential Jew of the last 1000 years. While covering many aspects of his religious philosophy, the central focus of these essays is the way Maimonides elucidated and expressed the universalistic thrust of the Jewish tradition. What is the secret that Maimonides hides? He himself tells us: the rabbis of the Talmud used the expression ma'aseh bereshit ("Ac-count of Creation") for what the Greeks called physics and used the expression ma'aseh merkavah ("Account of the Chariot") for what the Greeks called metaphysics. So why is this important? The consequences of these equations are momentous. Maimonides imports what we today would call science into the heart of Torah. This is allied to his universalism and to his conception of the com-mandments of the Torah as tools (which could in principle have been different), whose importance lies in the end they serve, and not in themselves. That being the case, true reward and punish-ment are not connected to behaviour, no matter how saintly or how vile, but to proper conceptions of God, crystallised in the 'Thirteen Principles'. Maimonides hid these secrets from his fellow Jews, not out of fear of reprisal (protected as he was by his good friend, al-Qadi at-Facil, he had no reason to fear them), but out of noblesse oblige. Exposing simple Jews (and their philosophically no less simple rabbis) to these truths could only lead to perplexity (in the best of circumstances) or to falling away from observance (in the worst of circumstances), neither of which Maimonides had any interest in promoting. One God wrote two books, as it were: Torah and Cosmos. The truly devout Jew realises that he or she must study both books, or only have access to half of God's oeuvre.
Part I. Approaches to the study of Maimonides -- Introduction to part one, Approaches to the study of Maimonides -- Reading Rambam-approaches to the interpretation of Maimonides -- Strauss' Maimonides vs. Maimonides' Maimonides : could Maimonides have been both enlightened and Orthodox? -- The literary character of the Mishneh Torah : on the art of writing in Maimonides' Halakhic works -- Is Maimonides' ideal person austerely rationalist? -- Part II. Religious faith and dogma -- Introduction to part two: Religious faith and dogma -- Heresy and the nature of faith in medieval Jewish philosophy -- What is heresy? -- Maimonides' thirteen principles and the structure of the Guide of the perplexed -- Maimonides, Crescas, and Abravanel on Ex. 20:2 : a medieval Jewish exegetical dispute -- Could Maimonides get into Rambam's heaven? -- Returning the crown to its ancient glory : Marc Shapiro's the limits of Orthodox theology : Maimonides' thirteen principles reappraised -- The virtue of faith -- Part III. Science and Torah -- Introduction to part three: Science and Torah -- On the status of the astronomy and physics in Maimonides' Mishneh Torah and Guide of the perplexed : a chapter in the history of science -- Maimonides on the science of the Mishneh Torah : provisional or permanent? -- Maimonides' allegiances to science and Judaism -- Faith, science, and orthodoxy -- Part IV. Universalism -- Introduction to part four: Universalism -- Chosenness not chauvinism : Maimonides on the chosen people -- Was Maimonides truly universalist? -- Maimonides' true religion : for Jews, or all humanity? -- Spirituality and a life of holiness : how one lives a holy life and who can do it.
Includes bibliographical references (pages 359-388) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Maimonides, Moses, -- 1135-1204.; Maimonides, Moses, -- 1135-1204.; Maimonides, Moses; RELIGION -- Judaism -- Sacred Writings; Philosophie; Thora; Religion; Philosophy & Religion; Judaism; Electronic books; Electronic book